Jill: A Flower Girl - Meade, L. T., 1854-1914; Townsend, F. H. (Frederick Henry), 1868-1920 (Salt Lake City, UT : Project Gutenberg, 2013)
"Jill: A Flower Girl" by L.T. Meade is a novel written in the late 19th century. The story revolves around the life of a young girl named Jill, who sells flowers in London and lives with her mother and two younger brothers in a modest flat. As the narrative begins, Jill navigates the stark contrast between the opulence of the upper classes and her own struggles, exploring themes of love, loyalty, and hardship as she grapples with her mother$1 (Bs struggles with alcohol and the challenges of caring for her family. The opening portion of the book introduces readers to the vibrant world of London during the season, juxtaposing the glamor of the high society with the impoverished lives of Jill and her family. Jill's deep admiration for the elegant ladies and gentlemen she observes from the street reflects her longing for a better life, while her commitment to her mother and determination to protect her from judgment drive her actions. The scene quickly unfolds to showcase Jill's compassionate nature, as she rushes to aid her inebriated mother, Poll, who faces a painful reality. This initial glimpse sets the stage for Jill's internal struggles, her aspirations for a loving marriage with Nat, and the poignant dynamics of her family life. (This is an automatically generated summary.)s
Release date is 2013-07-08
Produced by Nick Hodson of London, England
Keywords: Young women -- Juvenile fiction; Children of alcoholics -- Juvenile fiction; London (England) -- Social conditions -- 19th century -- Juvenile fiction; Working class -- Juvenile fiction